Relationship Between Mother's Level of Knowledge About Dental Health Maintenance and Dental Caries in Pre-School Age Children - Dian Tiara; Ganis Indriati; Sofiana Nurchayati (CV. Rayyan Dwi Bharata, 2023)
Introduction: Dental caries in pre-school aged 3-6 years often occurs due to one of the main factors, namely the lack of knowledge of parents, especially mothers. The purpose of this study was to determine the relationship between the level of mother's knowledge about maintaining dental health and the incidence of dental caries in pre-school-aged children. Methods: This research is a quantitative study with a cross sectional approach. Data collection techniques by observing dental caries and distributing questionnaires. The research sample is 123 respondents with total sampling technique. Results: most of the respondents were aged 25-34 years (50.4%), mother's education was tertiary as many as 68 respondents (55.3%), and the majority were housewives as many as 64 respondents (52.0%). The distribution of the description of the level of knowledge of the majority of mothers is sufficient, namely in 100 respondents (81.3%). Characteristics of the children showed that most of them were aged 5-6 years as many as 99 people (80.5%), and the majority were male as many as 72 children (58.5%). There were 108 children (87.8%) affected by dental caries. the majority of the mother's level of knowledge is sufficient, there are 104 children (100.0%) with dental caries. The results of the fisher exact test analysis found that there was a relationship between the level of knowledge of mothers about maintaining dental health and the incidence of dental caries in pre-school children (p value 0.000 Î± 0.05). Conclusion: Mother's level of knowledge influences the incidence of dental caries in pre-school children.